Jugoslavija – država neuspjelog nacionalizma / Yugoslavia – A State of Failed Nationalism - Kamberović, Husnija (Pregled: časopis za društvena pitanja / Periodical for social issues, 2024)
Text is a book review by Dejan Jović, Introduction to Yugoslavia, Zagreb: Fraktura, 2023., 490 pgs.